HUBUNGAN STRATEGI GURU TERHADAP KEMAMPUAN BACA AL-QUR’AN DI SMA DWIWARNA BOARDING SCHOOL PARUNG BOGOR - Mahfuzd, Khairunnisa; Ikhtiono, Gunawan; Nawawi, Kholil (Inspiratif Pendidikan, 2021)
The relation between teacher strategies and the ability to read the qur’an in High School of Dwiwarna Boarding School of Parung Bogor.. Skripsi. Major of Islamic Religious Education. Islamic Religious Faculty of Ibn Khaldun University. The Mentors : Gunawan Ikhtiono, Kholil Nawawi. The teacher strategy is a learning activity that must be used by teachers and students so that learning objectives can be achieved effectively and efficiently. The learning strategy is an action plan (a series of activities) including the use of methods and the use of various resources or strengths in learning. Therefore, it is reason for PAI teachers to be able to facilitate their students by teaching the al-qur’an in accordance with the teaching strategy. Because the information will be well received by students and learning can achieve optimal results. Therefore, this study aims to determine how the relationship between teacher strategies and the ability to read the qur’an at SMA Dwiwarna Boarding School Parung Bogor. This study uses a quantitative approach. Technique school Parung Bogor, amounting to 95 students. The data analysis technique in this research is SPSS 23.0 for windows. Based on the result of above analysis can be summarized that variable correlation value X and Y are 0,90, if observed from interpretation table the value that is gotten is 0,90 which is located between 0,70-0,90. Viewed from data interpretation it is included to strong correlation. Then by viewing table value on “r” with its significant value obtained “r” table is 0,2272. Therefore, on significant degree 5% “r” counting + 0,90> from “r” table = 0,2272, it means alternate hypotheses (Ha) is received and (Ho) is rejected. So, there is significant relation between teacher strategies and the ability to read the qur’an in High School of Dwiwarna Boarding School of Parung Bogor.